A Pilot Randomized Control Trial With the Probiotic Strain Lactobacillus rhamnosus GG (LGG) in ADHD: Children and Adolescents Report Better Health-Related Quality of Life - Kumperscak, Hojka Gregoric; Gricar, Alja; Ülen, Ina; Micetic-Turk, Dusanka (Frontiers in Psychiatry, 2020)
Objectives: This double-blind pilot randomized placebo-controlled trial examined the possible effect of the probiotic strain Lactobacillus rhamnosus GG ATCC53103 (LGG) on symptoms of attention-deficit/hyperactivity disorder (ADHD), health-related quality of life (QOL), and serum levels of cytokines in children and adolescents with ADHD. Methods: This trial evaluated 32 drug-naive children and adolescents aged between four and 17 years with a diagnosis of ADHD. The study subjects were randomly assigned to either the group that received LGG or the group that received the placebo. Assessments, comprising the ADHD Parent-Report Rating Scale-IV: Home Version; the Child Self-Report and Parent Proxy-Report of the Pediatric Quality of Life Inventory™ (PedsQL™) 4.0 Generic Core Scale; the Parent Form (CBCL/6-18) and the Teacher Report Form (TRF) of the Child Behavior Checklist (CBCL) for ages 6-18 of the Achenbach System of Empirically Based Assessment (ASEBA); and the serum cytokines; were compared between the groups at the baseline and after three months. Results: There was a statistically significant improvement in the PedsQL Child Self-Report Total Score after three months of treatment in the probiotic group (p = 0.021), whereas there was no improvement in the placebo group (p = 0.563). The results of psychometric parameters assessed by parents and teachers are not so straightforward. There were statistically significant differences in the levels of serum cytokines between the groups after the three-month treatment period: IL-6 in both the probiotic (p=0.004) and the placebo groups (p=0.035); IL-10 (p = 0.035); IL-12 p70 (p = 0.025); and TNF-α (p = 0.046) in the probiotic group only. Conclusions: Children and adolescents with ADHD who received LGG supplementation reported better health-related QoL compared to their peers who received the placebo. This suggests that LGG supplementation could be beneficial. The results were ambiguous when parents and teachers conducted the psychometric tests. The results on differences in the levels of inflammatory cytokines were not straightforward. Based on these results, we propose some study modifications: a longer observation period (6-12 months); inclusion of more children’s self-report assessments; recruitment of non-drug naive patients and the possible omission of serum cytokines measurements.